2019
DOI: 10.3389/fpsyt.2019.00229
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Employment on Delinquent Behavior Among Youth in Hidden Situation

Abstract: This study examines the effect of employment on delinquent behavior among young people in “hidden situations”. Both quantitative and qualitative methods were used, and 588 young people in these hidden situations were investigated. Results showed that some of them had employment; their employment status constituted a mediating effect on preventing them from being involved in delinquent behavior. Also, participants who had work explained the reasons for not being involved in delinquent behavior. These results re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…As for the other risk and protective factors included in our model, our results revealed that in accordance with previous research (Chan 2019;Khoury-Kassabri et al 2019;Mohammad and Banse 2023;Swisher and Shaw-Smith 2015;Zhang et al 2014;Zhao et al 2023), high impulsivity and arrest of a family member are associated with higher levels of juvenile delinquency. Likewise, religiosity (relationship with God), parental attachment, attachment to the neighbourhood, employment and married parents all predict lower levels of juvenile delinquency.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As for the other risk and protective factors included in our model, our results revealed that in accordance with previous research (Chan 2019;Khoury-Kassabri et al 2019;Mohammad and Banse 2023;Swisher and Shaw-Smith 2015;Zhang et al 2014;Zhao et al 2023), high impulsivity and arrest of a family member are associated with higher levels of juvenile delinquency. Likewise, religiosity (relationship with God), parental attachment, attachment to the neighbourhood, employment and married parents all predict lower levels of juvenile delinquency.…”
Section: Discussionsupporting
confidence: 91%
“…The second set of independent variables consists of sociodemographic measures, which were also found to be correlated with juvenile delinquency (Antle et al 2020; Chan 2019; Zhao et al 2023). These include “age”, “employment” (0 = no, 1 = yes), “parental marital status” (0 = not married, 1 = married), and “family member arrest by the police” (0 = no, 1 = yes).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived chronic social adversity was also shown to be correlated with depression, security and sense of control significantly, and it could predict one's PTSD symptoms significantly (Zhang, Cody, et al, 2017;Zhang, Ding, et al, 2017). According to the standpoint of general strain theory (GST), individuals who experience social adversity always become desperate and tend to perform deviant behaviors which refers to the ones that violates social norms and behavioral standards, or triggers negative reactions from others (Chan, 2019). In other words, social adversity is a direct factor for deviant behavior (Agnew, 1992(Agnew, , 2017Yang, 2003).…”
Section: Perceived Chronic Social Adversity and Suicidal Ideationmentioning
confidence: 99%
“…An extreme example of this is the ‘8050 crisis’ in Japan, which refers to the phenomenon that parents entering their 80s, because of physical, cognitive, and financial restrictions, can no longer take care of their hikikomori offspring (who have been living in seclusion for many years and are already in their 50s; Yamazaki et al, 2021 ). Chris did not rely on support of others; he survived his self-chosen exile by committing multiple crimes, as a result of which he was ultimately prosecuted in the legal justice system (see also Chan, 2019 ). Given associated difficulties, we tend to consider ESW as a clinically relevant problem.…”
Section: Introductionmentioning
confidence: 99%